The Effect of Insomnia on Tinnitus. (October 2014) - Miguel, George S.; Yaremchuk, Kathleen; Roth, Thomas; Peterson, Ed
Objective: The objective is to see how chronic tinnitus sufferers who are unmanageable to maximized medical therapy can benefit by decreasing their subjective complaints from a sleep evaluation and treatment. However, the proper identification of these particular patients has not been described well in the literature when attempting to correlate these 2 diagnoses. Thus, tinnitus patients with and without insomnia, based on ICD-9 diagnosis, were evaluated using the Tinnitus Reaction Questionnaire and Insomnia Severity Index to determine correlations between insomnia and tinnitus. Methods: Patients with a diagnosis of tinnitus and tinnitus along with insomnia who were treated at our institution from 2009 to 2011 were identified. Tinnitus Reaction Questionnaire and Insomnia Severity Index responses were obtained through written and telephone interviews. A Pearson product moment correlation was used to determine the effect of insomnia on tinnitus. Additional analyses identified whether Tinnitus Reaction Questionnaire scores were associated with a possible benefit from an evaluation for insomnia in tinnitus patients. Results: A total of 117 patients met inclusion criteria. A significant correlation was found between the Insomnia Severity Index score and Tinnitus Reaction Questionnaire severity ( r = 0.64; P = .001). Tinnitus Reaction Questionnaire severity was shown to be a good predictor of sleep disturbance and good in predicting group association, especially the "emotional" subscore component (sensitivity 96.9% and specificity 55.3% for identifying tinnitus patients with insomnia). The greater the insomnia disability as exhibited by an elevated Insomnia Severity Index score, the more severe the patient's complaints were regarding the tinnitus. Conclusion: Results suggest that if the emotional score on the Tinnitus Reaction Questionnaire is ≥ 15, the Insomnia Severity Index may be useful to identify patients who may benefit from further treatment and evaluation of insomnia. The robust correlation between the Tinnitus Reaction Questionnaire and Insomnia Severity Index objectively showed that patients with insomnia have an increased emotional distress associated with their tinnitus. Both questionnaires can be used together with a high degree of specificity and sensitivity in predicting tinnitus patients with an underlying sleep disturbance.